Modification of structural and functional characteristics of casein treated with quercetin via two interaction modes: Covalent and non-covalent interactions. (April 2023) - Ke, Chuxin; Liu, Bingshuo; Dudu, Olayemi Eyituoyo; Zhang, Shaoqi; Meng, Lu; Wang, Yu; Wei, Wanlinhao; Cheng, Jinju; Yan, Tingsheng
Abstract: Preparation of complexes via interactions between proteins and polyphenols has become one of the methods to effectively improve utilization of proteins. In this study, the structural and functional characteristics modification of casein treated with different concentrations of quercetin (10, 20, 40, 80 and 160 μmol/g protein) via covalent and non-covalent interactions were investigated. Results revealed that covalent complexes had lower sulfhydryl group content and higher quercetin binding capacity than non-covalent ones at the same quercetin concentration. This was consistent with the results of fluorescence spectroscopy which revealed higher fluorescence quenching constant and binding sites number for the covalent complexes. Fourier transform infrared spectroscopy demonstrated similar secondary structural changing trend for covalent and non-covalent complexes. The α-helix, β-turn and random coil contents increased with increasing quercetin concentration while β-sheet content decreased. Addition of quercetin decreased surface hydrophobicity of the complexes, regardless of covalent or non-covalent interactions. Casein solubility was improved in covalent interaction, while the non-covalent interaction impaired it. Quercetin treatment improved foaming activity, emulsifying activity and antioxidant activity while decreasing foaming stability and emulsifying stability. The results could provide a theoretical foundation for potential applications of casein-quercetin complexes in the food industry. Graphical abstract: Image 1 Highlights: Properties of covalent and non-covalent complexes of casein-quercetin were studied. Secondary structural alterations have similar trends via the two interaction modes. Covalent interaction between casein and quercetin was stronger than non-covalent. Covalent interaction improved casein solubility while non-covalent impaired it. Quercetin treatment improved FA, EAI and antioxidant activity but decreased FS and ESI.